Factor analysis of user satisfaction: A special reference to the library, University of Jaffna, Sri Lanka - Sivathaasan, N.; Chandrasekar, K. (My University, 2013)
Measuring user satisfaction is important in terms of survival of an academic library. The primary aim of this paper is to investigate the factors determining satisfaction of users who use the academic library. This study was carried out at the University of Jaffna, Sri Lanka among the library users. Data was collected by distributing a questionnaire to users of the library, those who visited to the library during a particular period. The study was exploratory in nature and employed factor analysis to identify the important factors of user satisfaction in relation to library facilities and services. Results revealed that nine factors are considered important in determining user satisfaction. Among those, most important factors are printing facilities, periodicals, reading table and chairs, opening hours, library orientation programme. In addition, factors extracted from the analysis accounted for 64.461 % of the total variability.
Keywords: User satisfaction; Academic libraries; Library facilities and services; Factor Analysis